(untitled) (Kairaranga, 2023)
Mauri Tui Tuia is a professional development programme established by the first and second authors who are a Registered Arts and Dance Movement Therapist and a Registered Music Therapist respectively. Mauri Tui Tuia seeks to empower educators to develop a kete of tools to support children in building resilience and maintaining wellbeing, through the medium of trauma-informed music and dance movement therapies. In this paper we discuss the theories that underpin the mahi (work) and give a broad overview of some of the ways our unique collaborative practices can potentially provide sustainable support for our communities in the wake of traumatic events, including the Covid-19 pandemic.